Biaxially Textured Titanium Thin Films by Oblique Angle Deposition: Conditions and Growth Mechanisms. Issue 2 (12th December 2019) - Liedtke-Grüner, Susann; Grüner, Christoph; Lotnyk, Andriy; Gerlach, Juergen W.; Rauschenbach, Bernd
Abstract : Growing highly crystalline nanowires over large substrate areas remains an ambiguous task nowadays. Herein, a time‐efficient and easy‐to‐handle bottom‐up approach is demonstrated that enables the self‐assembled growth of biaxially textured Ti thin films composed of single‐crystalline nanowires in a single‐deposition step. Ti thin films are deposited under highly oblique incidence angles by electron beam evaporation on amorphous substrates. Substrate temperature, angle of the incoming particle flux, and working pressure are varied to optimize the crystallinity in those films. Height‐resolved structure information of individual nanowires is provided by a transmission electron microscopy (TEM) nanobeam, high‐resolution TEM, and electron diffraction. Ti nanowires are polycrystalline at 77 K, whereas for ≥300 K, single‐crystalline nanowires are tendentially found. The Ti crystals grow along the thermodynamically favored c ‐direction, but the nanowires' tilt angle is determined by shadowing. Biaxially textured Ti thin films require a certain temperature range combined with highly oblique deposition angles, which is proved by X‐ray in‐plane pole figures. A general correlation between average activation energy for surface self‐diffusion and melting point of metals is given to estimate the significant influence of surface self‐diffusion on the evolution of obliquely deposited metal thin films. Abstract : Herein, the formation of biaxially textured, columnar titanium thin films on amorphous substrates at different temperatures (77 K ≤  T Sub  ≤ 873 K) is investigated. The Ti columns tend to grow as single crystallines. A relation is derived that allows to estimate the average adatom surface self‐diffusion length for a given substrate temperature.